(untitled) (Homoeopathy for All, 2022)
Osteoarthritis (OA) is a disease marked by progressive joint failure in which all structures of the joint have undergone pathologic change. The pathologic changes of OA are hyaline articular cartilage loss accompanied by increasing thickness and sclerosis of the subchondral bony plate, outgrowth of osteophytes at the joint margin, stretching of the articular capsule, and weakness of the muscles bridging the joint. There are numerous pathways that lead to OA, but the initial step is often joint injury in the setting of a failure of protective mechanisms. Osteoarthritis most commonly affects the hands, lower back, neck, and weight-bearing joints such as knees, hips, and feet.